Parental job loss and children's health: Ten years after the massive layoff of the SOEs' workers in China - Hong Liu; Zhong Zhao (Institute for the Study of Labor (IZA), 2011)
Beginning in the mid 1990s, China sped up its urban labor market reform and drastically restructured its state-owned enterprises (SOEs), which resulted in massive layoff of the SOEs' workers and a high unemployment rate. In this paper, we investigate the impact of the parents' job loss on the health of their children, using six waves of the China Health and Nutrition Survey covering the period from 1991 to 2006. We find that paternal job loss has a significant negative effect on children's health, whilst maternal job loss has no significant effect. The rationale behind the findings is that the income loss resulting from maternal job loss is much smaller; at the same time, the unemployed mothers are likely to increase the time they devote to care of their children, and this may alleviate the negative effect resulting from maternal job loss. Our findings are robust to various specifications.
urn:nbn:de:101:1-201107283711
Keywords: I12; J63; N35; J13; 330; children's health; job loss; Grossman's model; China